Improving Students Listening Comprehension Through Topdown Technique - Dina Syarifah Nasution (PT FORMOSA CENDEKIA GLOBAL, 2022)
The research aims to measure the implementation of topdown technique on improving students ability at listening comprehension of grade XIak1 at SMKN 1 Panyabungan.The method of this research was Classroom Action Research. The participant in this classroom action research was 25 students of grade XIak1 at SMKN 1 Panyabungan. The instruments consisted of topdown technique, listening comprehension test, observation sheet, and interview, the data of this research was analyzed two method of data analysis. Quantitative data analyzed was used to examining and interpreting data from topdown technique and listening comprehension. The data taken from observation and interview was used qualitative data analysis. The research consisted of two cycles, before first cycles started, the researcher conducted pre test to know students listening comprehension real ability. First Cycle conducted after treatment given, due to the result of first cycle doesn`t improve in all aspect. Researcher continued to second cycles at the end of cycle. Three result test to be compared to know students improvement in listening comprehension. The result shows that the topdown technique better improves the students ability at listening comprehension. Students score were obtained from total score of correct answer which is converted to Toeic conversion scale. The findings on this study proved that teaching listening applying topdown technique improved students` listening comprehension. Significance improvement particularly in students ability to answer listening part one; matching pictures with statement. Based on the result of the study topdown technique to be recommended for the teacher in Vocational High School ( SMK ) to improve students` listening comprehension.